Analysis of hydrogen isotopes with quadrupole mass spectrometry. Issue 20 (16th May 2017) - Cao, Dawei; Peng, Shuming; Chen, Xiaojun; Hou, Jingwei; Chen, Ping; Xiao, Chengjian; Gong, Yu; Wang, Heyi
Abstract : Hydrogen isotope separation is one of the most critical technological problems in nuclear fusion research, and, in order to assess accurately the performance of hydrogen isotope separation, quantitative analysis of hydrogen isotopes takes priority and becomes the first essential problem to be addressed. Abstract : Hydrogen isotope separation is one of the most critical technological problems in nuclear fusion research, and, in order to assess accurately the performance of hydrogen isotope separation, quantitative analysis of hydrogen isotopes takes priority and becomes the first essential problem to be addressed. However, since hydrogen isotopes have almost identical shape, size, and chemical properties, separation and analysis of hydrogen isotopes is really not an easy task. By using the thermal-desorption spectroscopy (TDS) method, a quadrupole mass spectrometer (MS) was calibrated for the quantitative analysis of hydrogen isotopes in this paper with a methodic error less than ±3% using titanium hydride and titanium deuteride as the calibration standards. The linear response range of MS was extracted. Deviations that originated from the H + /D + /HD + species revealing a negligible influence on real H2 /D2 mixture analysis were also discussed. Due to the mass discrimination of the ion source and the isotopic fractionation effect of the molecular pump, the actual sensitivity of MS towards H2 and D2 is not the same, revealing some deviation from theoretical results.